Littoral and sub-littoral sediments in Lake Biwa -Division based on a thermal structure of the lake and their possible roles in the lake ecosystem - MURASE, Jun (Japanese Journal of Limnology (Rikusuigaku Zasshi), 2002)
The bottom of Lake Biwa, the largest lake in Japan, is divided into littoral, sub-littoral, and profundal zones based on the thermal structure of the lake water. The features of element metabolism and dynamics in the littoral and sub-littoral surface sediments are discussed in comparison with the profundal sediment. The littoral zone, where the bottom is covered with epilimnetic water, is characterized by lower organic content and higher temperature compared to the profundal zone. Higher microbial activities in the littoral sediment due mainly to the high temperature can cause oxygen depletion in the bottom water especially in summer. The bottom sediment of the sub-littoral zone, which is covered with a thermocline, is subject to resuspension by an internal wave such as seiche. Resuspension of the sub-littoral sediment might be one of the internal sources of phosphorus loading as well as methane to lake water. Seasonal changes in the thermal structure of lake water cause a shift in the littoral and sub-littoral zones from shallower to deeper parts of the lake. Studies on element dynamics in the sediment of the respective zone are necessary to understand the role of the lake bottom in the lake ecosystem.